Dynamics of investor communication in equity crowdfunding - Gregor Dorfleitner; Lars Hornuf; Martina Weber (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2017)
In crowdfunding, start-ups can voluntarily communicate with their investors by posting updates. We investigate whether start-ups strategically use updates, which were previously shown to increase investments. To this end, we use hand-collected data of 751 updates and 39,036 investment decisions from the two major German equity crowdfunding portals Seedmatch and Companisto. We find evidence for strategic communication behavior of startups during an equity crowdfunding campaign. During the funding period, start-ups post updates with linguistic devices that enhance the group identity and the group cohesion. Furthermore, the probability of an update during the funding period increases with a strong competition of other contemporary crowdfunding campaigns.
Keywords: 330; Crowdfunding; Investor Communication; Entrepreneurial Finance; Sentiment Analysis; Linguistic Devices